Pengaruh Kepribadian Karyawan Dan Etika Kerja Islam Terhadap Kinerja Pada Baitul Maal Wat Tamwil Binaan Pinbuk Tulungagung - Fatkhur Rohman Albanjari (Musyarakah: Journal of Sharia Economic (MJSE), 2023)
This study aims to determine the effect of personality traits and Islamic work ethics on employee performance in Baitul Maal Wat Tamwil guidance by PINBUK Tulungagung. Method of this research is quantitative. This research conducted by associative research with the number of subjects are 62 people. Data collection in the form of questionnaires. Data analysis was carried out using path analysis and SPSS version 20 statistical program. The results of this research indicate that locus of control has a positive and significant effect on employee performance. Furthermore, self-esteem also has a positive and significant effect on the performance of BMT’s employees. Self-monitoring also has positive and significant results on performance. Islamic work ethics also have a positive and significant effect on employee performance. Locus of control, self-esteem, and self-monitoring have a greater positive and significant effect on employee performance through Islamic work ethics.